Drug-coated Balloons for Small Coronary Vessel Interventions: A Literature Review - Thomas Nestelberger; Raban Jeger (Interventional Cardiology: Reviews, Research, Resources)
Newer-generation drug-eluting stents (DES) are the standard of care for the treatment of symptomatic coronary artery disease. However, some lack of efficacy has been reported in small coronary arteries based on higher rates of target lesion restenosis, thrombosis and MI resulting in repeated interventions. Drug-coated balloons (DCBs) are an established treatment option for in-stent restenosis in both bare metal stents and DES and they can deliver an anti-proliferative drug into the vessel wall without implanting a stent. DCBs are a promising technique for selected de novo coronary lesions, especially in small vessel disease. In this article, the current evidence for the treatment of small vessel disease with DCBs will be reviewed.